Advertisement Remove all ads

Solve : (A + B)²X² – (A + B)X – 6 = 0; a + B ≠ 0 - Mathematics

Sum

Solve : (a + b)²x² – (a + b)x – 6 = 0; a + b ≠ 0

Advertisement Remove all ads

Solution

`(a + b)^2x^2 - (a + b)x - 6 = 0; a + b != 0`

`=> (a + b)^2x^2 - 3(a + b)x + 2(a + b)x - 6 = 0`

`=> (a + b)x[(a + b)x - 3] + 2[(a + b)x - 3] = 0`

`=> [(a + b)x - 3][(a + b)x + 2] = 0`

=> (a + b)x - 3 = 0 or (a + b)x + 2 = 0

`=> x= 3/(a + b) or x = (-2)/(a + b)`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 5 Quadratic Equations
Exercise 5 (E) | Q 15 | Page 67
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×